Pseudocapacitive behavior of the Fe 2 O 3 anode and its contribution to high reversible capacity in lithium ion batteries - Xiang, Yimo; Yang, Zhigao; Wang, Shengping; Hossain, Md. Shahriar A.; Yu, Jingxian; Kumar, Nanjundan Ashok; Yamauchi, Yusuke (Nanoscale, 2018)
Pseudocapacitance, which is the storage of charge based on continuous and fast reversible redox reactions at the surface of electrode materials, is commonly observed for electrodes in lithium ion batteries, especially for transition metal oxide anodes. In this report, bare Fe 2 O 3 of granular morphology (∼30 nm in diameter) with high purity and decent crystallinity as well as recommendable electrochemical performances is fabricated hydrothermally and employed as the subject to clarify pseudocapacitive behavior in transition metal oxide anodes. Electrochemical technologies such as galvanostatic charging/discharging, differential capacity analysis (d Q /d V ) and the power law relationship ( i = aν b ), which can distinguish pseudocapacitive behaviors of an electrode reaction were employed to analyze the electrodes. Reversible capacities of ∼120 mA h g −1 (0.117 F cm −2 ) for Fe 2 O 3 were found within particular electrochemical windows (2.3–3.0 V, 0.3–0.8 V for discharging and 2.2–3.0 V, 0.3–1.3 V for charging). A new direction of optimizing the capacities, rate and cycling performances for lithium ion batteries is pointed out with connections between the pseudocapacitive behavior and morphologies of surfaces as well as structures of the electrodes.